Come on, carry on: Phrasal verb use in undergraduate writing at a South African university - Immelman, Susan; Cooper, Patricia Anne (Journal for Language Teaching, 2023)
The phrasal verb plays an important role in the attainment of English proficiency. However, it has been recognised as problematic for learners of English worldwide for various reasons, with the result that learners tend to employ avoidance strategies when confronted with the phrasal verb. Use of the phrasal verb (PV) has not been researched to any great extent in the South African environment, a limitation that this study seeks to address. Using a corpus of undergraduate writing, PV use by South African first- and second-language speakers of English is investigated and reported on. The results differ from previous research in finding that second-language speakers are most likely to use phrasal verbs in their first year of undergraduate study, and that this tendency tapers off as their studies progress. First-language students show a similar but less marked pattern of PV use. The results also indicate a preference for one-word alternative verbs by both groups, which again contrasts with research conducted elsewhere, which found that first-language students displayed a preference for PV use over one-word alternative verbs. It is suggested that further research is required to verify these results.